Real and monetary convergence within the European Union and between the European Union and candidate countries: A rolling cointegration approach - Josef C. Brada; Ali M. Kutan; Su Zhou (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
We use rolling cointegration to measure the convergence of base money, M2, the consumer price index and industrial output between two reference countries, Germany and France, and recent EU members and some transition economy candidates. Counties that recently joined the EU exhibit time-varying cointegration with the reference countries over much of the 1980-2000 sample period. Cointegration for the transition economies was comparable for M2 and prices, but less so for monetary policy and industrial output. This suggests that a peg to the Euro upon accession is feasible for the East European candidates, but the benefits of joining the Euro zone are as yet limited.
Keywords: F15; F36; F42; 330; European Union; convergence; currency areas; enlargement; cointegration; policy coordination